"Autism-to-autism conversation": exploring recognition and (re)construction of autistic identity in higher education - Klotz, Reese Duff, author; Aoki, Eric, advisor; Faw, Meara, committee member; Hepburn, Susan, committee member (Colorado State University. Libraries, 2026)
Since the earliest conceptions and models of autism were created, U.S. American society has consistently looked upon autistic people with shame, hostility, and misinformed assumptions of what being autistic means to autistic individuals. In higher education environments, these stigmatizing and misleading narratives of autistic lives often lead to inequitable access to social and academic opportunities, detrimental impacts upon autistic students' wellbeing, and the overall failure of academic institutions to reform their perceptions of what autistic students are capable of accomplishing. Understanding how autistic students themselves construct and voice their identities and lived experiences in higher education is critically needed. This thesis centers autistic university students' accounts of how they experience autistic identity to explore the ways autistic identity is enacted and consequently (re)constructed in interactions between autistic peers. The findings illustrate autistic students' profound and nuanced understandings of how their autistic identities manifest in their self-perceptions, their behaviors, their relationships with autistic peers, and their experiences of autistic community. These narratives generate powerful resistance against stigmatizing discourses around autistic communication and offer valuable considerations for how higher education institutions can facilitate social and systemic justice for their autistic students.
Autism-to-autism conversation: exploring recognition and (re)construction of autistic identity in higher education
Keywords: autistic communication; social identity; higher education; autism